TEXT CULTURAL SPECIFICITY: TRANSLATABILITY AND ELIMINATION - E. M. Maslennikova (Концепт: философия, религия, культура, 2017)
When translating a literary text full of culturally specific features, interpreters try to explicate the implicit. It may turn into their interpretation of the source text, as well as paraphrasing and replacement of what is unclear or misunderstood by “understandable” ideas and concepts. Texts meanings’ increment occurs when translators convert the initial system of concepts and images created by the author. Texts’ inclusiveness into the semiosphere is supported by citations, headings and titles, epigraphs, allusions, reminiscences, various symbols of culture, cultural memory, so-called genre memory, etc., referring to the prototext and / or substituting it in a particular text. In fiction the WORD specifies and directs the processes of meanings’ reception and meanings’ construction that are particular for every reader. In literary texts the WORD appears as a means of its cultural specification and sets out the limits of its interpretive range. The reader starts to reconstruct the author’s intentions trying to enter the WORD’s worlds. In some cases the WORD can be a part of the author’s particular “language” known only for the initiated readers. The level of the highest practicable translatability also depends on the orientation of the author to a particular subject area and associated specialized knowledge. Modern translation theory suggests the idea of fundamental translatability of any text due to the fact that there can be untranslatable language, thematic and stylistic phenomena, but untranslatability is eliminated at the level of the text. Translatability and untranslatablity of cultural references and cultural codes is related to specific lacunar concepts. The article discusses how to reproduce and recreate cultural specification of a literary text in the process of translation.